ANTIMICROBIAL POTENTIAL OF FIVE MEDICINAL PLANT EXTRACTS AGAINST THREE PATHOGENIC BACTERIA - S. AMBARISH; S. S. INGALHALLI; N. V. BIRADAR; K. SOUMYARANI; K. MITHILA; S. LALITA; J. SHRINATH; M. DATTACHAITANYA (The Bioscan, 2011)
Medicinal plants are nature’s gift to cure a number of diseases in human beings and animals. Herbal medicine represents one of the most important fields of traditional medicine all over the world because of its ecofriendly nature. To promote the proper use of the herbal medicines and to determine their potential as a source for new drugs, it is essential to study medicinal plants which have folklore reputation in a more intensified way. The assessment of antimicrobial potential of five selected medicinal plant extracts dominant in Dharwad region, namely Catharanthus roseus, Azadhirachta indica, Eucalyptus globulus, Mimosa pudica and Costus igneus against three pathogenic bacteria Escherichia coli, Staphylococcus aureus and Bacillus subtilis were carried out. Antimicrobial activity of various plant extracts were tested by Agar well diffusion method. In extraction of antimicrobial compounds from the medicinal plant materials, the solvents alcohol, acetone and water were used. The plant extracts tested exhibited different degree of antimicrobial activity against gram +ve and gram -ve pathogenic bacteria. The Catharanthus roseus, Eucalyptus globulus, Mimosa pudica, Costus igneus plant extracts showed very effective degree of inhibition and Azadhiracta indica showed moderate degree of inhibition against three pathogens in alcohol and acetone. The aqueous extracts of the plants were not showed degree of inhibition except Azadhiracta indica, Eucalyptus globulus against Staphylococcus aureus. AND M. DATTACHAITANYA